MEDIA RESPONSE ON IRAN'S ATTACK AGAINST ISRAEL: Western, Middle Eastern, and Indonesian Media Discourse - Sri Rejeki, Erlin Kurnia; Basit, Abdul; Adhim, Fathul (Ulul Albab: Jurnal Studi Islam, 2024)
This article discusses media responses to Iran's attack on Israel, comparing the narrative constructed by Western, Middle Eastern, and Indonesian media. It investigates how different perspectives and media biases from different regions shape the discourse surrounding the event. Using discourse analysis, this study provides an in-depth analysis of media texts, focusing on structure, language use, and the contextualization of ideologies in news coverage. This analysis explores how media from the West, the Middle East, and Indonesia framed the conflict and identifies lessons from these differing narratives in shaping public perception. The findings aim to contribute to understanding the dynamics of media discourse in international news, and to enrich the fields of communication and international relations by highlighting the media’s role in constructing global conflict narratives. The results reveal that Western media emphasize diplomatic and humanitarian perspectives, Middle Eastern media focus on themes of struggle and ideology, and Indonesian media highlight political and social impacts at the local level. These differences reflect how discourse is shaped by diverse regional interests and viewpoints, influencing how communities in each region perceive and understand such conflicts.